Cystoid macular changes on optical coherence tomography in a patient with maternally inherited diabetes and deafness (MIDD)-associated macular dystrophy. (3rd September 2017) - Qian, Cynthia X.; Branham, Kari; Khan, Naheed; Lundy, Steven K.; Heckenlively, John R.; Jayasundera, Thiran
ABSTRACT: The clinical presentation and optical coherence tomography findings in a patient with maternally inherited diabetes and deafness (MIDD) are presented to highlight the presence of macular cystoid spaces in some patients with this disease. Typically, patients with MIDD demonstrate progression of a pigmentary maculopathy into areas of geographic macular atrophy. At the time of initial visit, the 30-year-old patient had large macular cystoid changes in addition to retinal pigmentary changes in both eyes. The cystoid changes responded to treatment with systemic immunosuppression and a topical carbonic anhydrase inhibitor (CAI), recurred when treated with topical CAI monotherapy, and finally resolved after an intravitreal triamcinolone acetonide injection. Over time, the retinal atrophy continued to progress, but the macular cysts did not recur. The patient received systemic immunosuppression for renal transplantation due to renal failure resulting from focal glomerulosclerosis. There was no evidence of diabetic retinopathy at any time during the five-and-a-half-year follow-up, and the patient retained good visual acuity in both eyes.